PERBANDINGAN ANGKA KESEMBUHAN ANTARA PASIEN COVID-19 YANG MEMILIKI KOMORBID DIABETES MELITUS DENGAN PASIEN COVID-19 TANPA KOMORBID DIABETES MELITUS DI RUMAH SAKIT NATAR MEDIKA NATAR TAHUN 2021 - Firhat Esfandiari; Doni Rahman Nurdiana; Tusy Triwahyuni; Toni Prasetia (Medula, 2022)
COVID-19 is a disease caused by the SARS-CoV-2 virus. Most people infected with the virus can experience moderate to severe respiratory problems and recover without requiring special treatment. However, some will become severe and require medical treatment.Diabetes mellitus (DM) is a chronic disease that poses a challenge in the world of health, diabetes mellitus is one of the non-communicable diseases (PTM) which caused 1.6 million deaths in 2010. The cure rate among COVID-19 patients who have comorbid diabetes mellitus is higher. small compared to COVID-19 patients without comorbidities. Knowing the comparison of the cure rate of COVID-19 patients with diabetes mellitus as comorbid and COVID-19 patients without comorbidities at Natar Medika Hospital, Natar District, 2021. This study uses a descriptive-comparative research method with a cross sectional approach. Based on the results of this study, the majority of respondents were 71 respondents consisting of age > 45 years with a total of 50 patients (70.4%) the majority of respondents were women with 37 patients (52.1%) most patients with COVID-19 were without comorbid as many as 44 people (62%) of COVID-19 patients who recovered were more than COVID-19 patients who died, namely 59 patients (83.1%). In the results of statistical test analysis with Mann Whitney obtained p value = 0.000 (p <0.05) which means that there is a significant difference in the cure rate between COVID-19 patients who have comorbid diabetes mellitus and COVID-19 patients without comorbidities at Natar Hospital. Medika Natar in 2021.